Texas Almanac 2018-2019 - Plocheck, Robert; Alvarez, Elizabeth Cruce (Book collections on Project MUSE., 2018)
The Texas Almanac is a complete reference book on all things Texan: History, Environment, Weather, Astronomical Calendar, Recreation, Sports, Counties, Population, Elections, Government, Culture, Health, Science, Education, Business, Transportation, Agriculture, Pronunciation Guide, and Obituaries. Feature articles and updated data are presented in 752 pages with hundreds of color photos and maps.